POLA KOMUNIKASI PASANGAN SETELAH KONSELING PRANIKAH PADA CALON PENGANTIN ASN KOTA SURAKARTA - Jihan Hasna Salsabila; Sri Ernawati; Faqih Purnomosidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate and describe changes in couples’ communication after undergoing premarital counseling. The primary focus is on prospective brides and grooms who are Civil Servants (ASN) in Surakarta. Premarital counseling serves as a means to prepare couples for harmonious relationships, with communication being a crucial element. This study used a descriptive qualitative approach, where data were collected through observation, in-depth interviews, and document analysis of eight ASN couples who had undergone premarital counseling. The research findings indicate an improvement in couples’ communication, particularly in the areas of openness, empathy, and conflict resolution. Premarital counseling plays a crucial role in helping couples realize the value of good communication in creating harmony in the household. However, challenges such as workloads and differing perspectives continue to impact communication interactions. These findings provide input for premarital counseling providers and the government to improve the quality of counseling services for prospective brides and grooms, particularly among ASN. Keywords: Communication Patterns, Premarital Counseling, Prospective Brides and Grooms, ASN in Surakarta City.